Mobile Laboratory for Training in Network Technologies - Grega, W.; Papadourakis, G. (Elektronika ir Elektrotechnika, 2010)
Technological development has brought the use of networks in control to the mainstream. Ethernet-based systems are becoming an increasingly attractive technology as they combine large capacity and high speed with flexibility. New trends in control technology must be reflected in the respective teaching activity. In the response to the demands the concept of mobile laboratory was proposed and has been implemented by the consortium of university and industrial partners from six European countries and two partners from Turkey. The CoNeT (Cooperative Network Training) project described in this paper aims at training of automation engineers, maintenance engineers, process workers and students both graduate and undergraduate in modern industrial Ethernet technologies.